Refugees in higher education : debate, discourse and practice - Stevenson, Jacqueline; Baker, Sally (Great debates in higher education., 2024)
Despite growing attention and focus, the issues with refugee access, participation, and success in higher education detailed in the first edition stubbornly remain, magnified by intensifying international conflict, as well as the impacts of COVID on universities. The second edition of Refugees in Higher Education contains new sections focused on issues of race and racialisation, treatment of people seeking asylum in both national contexts, and international efforts to respond to issues with refugee access to higher education, including international educational complementary pathways, and national sanctuary movements. Offering an up-to-date review of the international literature, this new edition captures the contemporary forced migration, displacement, and resettlement policy and practice landscape - internationally and in the specific resettlement countries of the UK and Australia the 'post-COVID' higher education context - and what this highlighted about the participation of refugee students. A new case study brings real experience of educational pathways for refugees, alongside a greater focus on ethical engagement. This updated edition of Refugees in Higher Education provides a much-needed contemporary account of the context in which refugee education scholars, advocates, and students themselves are operating in, detailing how universities in Australia and the United Kingdom can extend access to refugee education globally.